Answer :

We have, (x + 1) = 0

x = - 1


Firstly, putting (x = - 1) in x3 – 2x2 + x + 2 we get:


= (- 1)3 – 2 (-1)2 + (-1) + 2


= - 1 – 2 – 1 + 2


= - 2


(x + 1) is not a factor of x3 – 2x2 + x + 2


Secondly, putting (x = - 1) in x3 + 2x2 + x - 2 we get:


= (-1)3 + 2 (-1)2 + (-1) – 2


= - 1 + 2 – 1 – 2


= - 2


(x + 1) is not a factor of x3 + 2x2 + x – 2


Thirdly, putting (x = - 1) in x3 + 2x2 – x – 2 we get:


= (-1)3 + 2 (-1)2 – (-1) – 2


= - 1 + 2 + 1 – 2


= 0


Hence, (x + 1) is a factor of x3 + 2x2 + x – 2


Thus, option C is correct

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x31</sRS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x3RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics